Organ of vision in children with fetal alcohol spectrum disorders - Grałek, Mirosława; Niwald, Anna; Piasecka, Katarzyna; Krzymianowska, Anna; Lipiec, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2024)
Fetal alcohol spectrum disorders (FASD) are a group of permanent birth defects resulting from maternal alcohol consumption during pregnancy, characterized by neurological, somatic, and mental abnormalities. Among them are changes in the organ of vision, including a decrease in visual acuity and other serious effects. FASD encompasses a range of distinct disease entities, each with its own specific symptoms. These are: fetal alcohol syndrome, partial fetal alcohol syndrome, alcohol-related neurodevelopmental disorders, and alcohol-related birth defects. There is no causal treatment for the disease. Maternal abstinence at all stages of pregnancy is a preventive measure. The best results in the treatment of children with FASD are achieved with individualized, personalized supportive therapy provided by interdisciplinary medical teams. The goals are to alleviate existing dysfunctions and to prevent secondary disorders that result from inadequate or absent medical assistance.